Análise de correlações entre tremor, degeneração celular e idade - Mansur, Paulo Henrique Garcia (2011)
The main problem of tremor is the damage caused to the quality of the life of patients, especially those at more advanced ages. There is not a consensus yet about the origins of this disorder, but it can be examined in the correlations between the biological signs of aging and the tremor characteristics. This work sought correlations between the osmotic fragility of erythrocytes and features extracted from electromyographic (EMG) activity resulting from physiological tremor in healthy volunteers (N=44) at different age groups (24-87 years). The osmotic fragility was spectrophotometrically evaluated by the dependence of hemolysis, provided by the absorbance in 540 nm (A54o), on the concentration of NaCl. The data were adjusted to curves of sigmoidal regression and characterized by the half transition point (H50), amplitude of lysis transition (dx) and values of A540 in the curve regions that characterize the presence of lysed (A1) and preserved erythrocytes (A2). The amplitude, frequency and approximate entropy was estimated from EMG signals detected with surface electrodes fixed on the extensor carpi ulnaris muscle during the movement of the hand of subjects holding up a laser pen towards an Archimedes spiral, fixed in a whiteboard, and from an acelerometer fixed at the pen. The evaluations were carried out with the laser pen at rest, at the center of the spiral, and in movement from the center to the outside and from outside to the center. The correlations among the parameters of osmotic fragility, tremor, gender and age were tested. Negative correlations with age were found for A1 and dx. With the hand at rest, a positive correlation with H50 was found for the approximate entropy. Negative correlations with H50 were found for the entropy with the hand in movement, as from the center to the outside or from the outside to the center of the spiral. In neurological healthy individuals, the increase in the erythrocyte osmotic fragility was associated with a decrease in the approximate entropy for rest tremor and with an increase of the entropy for movement tremor. This suggests that the neuromuscular degeneration associated with tremor entails also the mechanisms involved in the breakdown of structural homeostasis of the erythrocyte membrane.